O desenho do lugar: uma representação da territorialidade étnica - Santana Filho, Aderbal Pereira (2014)
During everyday activities, we mentally produce paths and/or routes full of information. This mental process once transfered to a piece of paper is called “mind map”, which is the recommended tool to understand what was lived and to introduce school cartography. At schools, cartography taught by teachers goes through a lot of challenges, due to the complexity existed around it. However, when the 12th grade student Hãhãhãi Pataxó of the Indigenous State School draws a symbolic map of his territory and his pathway between his house and school, are there represented, symbolic aspects, identity and cultural aspects, from the most significant elements to him. This research aimed to learn from the mental maps and semi-structured interviews the perception that indigenous student from the mentioned village has about their ethnic territory and the place of experience, both categories of geographical analysis. The survey was conducted in three different moments: first, in order to identify prior knowlegde, students wererequested to produce two mind maps, depicting the route that they make from their homes to school and of the territory of the village; the second was the pedagogical mediation performed by this teacher/researcher during Five meetings with didactic sequences about school cartography. At the last moment of post-mediation, once again, students were requested to produce the two mind maps, in order to compare them, then checking what changes occurred. The approach methodology used was the phenomenological, grounded in Humanistic Geography, with emphasis on Spatial Perception. To analyze the data, Semiotics was used in an attempt to understand the sign and phenomenology, the phenomenon, from a descriptive analysis of the drawings and their comprehension by the students’ explanations. After analyzing the data it can be concluded that in the drawings of the mind maps were present, not only the representation of the place and territory, but also the cartographic language empowerment, via the use of conventional cartographic elements as well as the perception representation enrichment, in which the lived world becomes of salutary importance for meaningful learning.